Análisis de factibilidad para mantener la rentabilidad económica de la Contrata Especializada JRC Ingeniería y Construcción SAC en la UM Minera del Sur- Arequipa 2019 - Quispe Condori, Helmer (2020)
The objective of this Thesis is to carry out a “Feasibility Analysis to maintain the economic profitability of the Specialized Contract JRC Ingeniería y Construcción SAC in Minera del Sur. The specialized mining contract JRC Ingeniería y Construcción SAC is in charge of carrying out the preparation of Levels, Cruises, Bypass, Ramps, Galleries from level 4890 to level 4340 with the aim that the company subsequently enters to exploit its pit by the method Bench & Fill. All operations are carried out entirely mechanized. The Southern Mining Unit and the JRC Engineering and Construction Specialized Contract have a contract, which the monthly physical goal for linear advance is 1500 linear meters linear meters per month. Due to calculation problems of proven and probable reserves, they were forced to reduce from 1,500 meters programmed monthly to 500 linear meters monthly, which the JRC Engineering and Construction Specialized Contract will have to assume the problem and see how to reach the economic profit margin that is 10%. The research is carried out under a descriptive, applicative methodology with an experimental research design and a hypothetical deductive method with a population made up of teams and labor, using the technique of observation and analysis of documents, the conclusion is reached “The Feasibility to maintain economic profitability, it was necessary to carry out a dimensioning of equipment and direct labor, reducing the LHD equipment and the Dumpers, as well as the labor force from the number of 292 workers to 150 total workers of the company and thus it was possible to improve profitability from 4.6% gross margin to 31% and also raise the level of compliance from 88.6% to 108%. Performing the profitability calculation of the VAN and the TIR which is 303,790.93 and 16% respectively giving a positive TIR of the Specialized Contract JRC Ingeniería y Construcción SAC.